Мы должны их спасти: [очерки о животных из Красной книги] / А. Г. Банников, В. Е. Флинт - Банников Андрей Григорьевич (Мысль, 1982)
Экземпляры: ЧЗ (20181022) / Инвентарный номер: 2869 / Цена: 0.60 / Сис.шифр: 57 / Авт.знак: Б23 / ГРНТИ: 34 / ББК: 57(069)